Strategizing in horizons and verizons: Distinguishing between mediators and firms' mediating functions. Issue 2 (12th June 2017) - Huemer, Lars
Abstract : Purpose: The study has two related objectives. At the firm level of analysis, the author proposes that a clearer distinction between firms' mediating functions and mediators could enhance the understanding of business network strategizing. Whereas firms' mediating functions have received attention in IMP research, less focus has been given to organizations whose core business is mediation. At the system level of analysis, the study complements the perception of a network horizon with that of a network verizon. Whereas the horizon is closely associated with work on firms' mediating functions, the network verizon is of particular interest to mediators. The paper aims to discuss these issues. Design/methodology/approach: This conceptual study combines IMP insights with strategic management theory. Findings: The notion of a network horizon is important for business network strategizing, but also influences the perception of relevant network structures. These structures tend to be characterized by sequential interdependencies and a long-linked technology, often associated with physical products and production facilities. The notion of a network verizon highlights a network "depth" that has been unnoticed by previous work, which has focused on how narrow or wide a firm's network horizon should be. The network horizon and the network verizon add strategizing options in terms of connecting key actors in the network to create additional value. Originality/value: This paper concerns how IMP scholars understand boundaries and firms, and how perceptions of these influence business network strategizing. The study articulates a distinction between firms' mediating functions and those organizations that fundamentally create value through mediating services. This distinction has system-level implications. In particular, the claim that the basis for a firm's strategizing is its network horizon is discussed. The author proposes the notion of a "network Verizon, " providing a boundary perception of specific relevance to mediators. The network verizon portrays a network depth beyond both sequential tiers in a supply chain and links between different supply chains.